Oxidative Stress in Fish: A Review (Journal of Scientific Research, 2020)
Apart from its beneficial properties of oxygen to cellular functions, it can cause some undesirable damages by the formation of ROS which can be neutralized by the formation of enzymatic and non-enzymatic antioxidants. Like any other vertebrate, these damages can be seen in fish which are exposed to various oxidative stressors. In fish, it may be brought by a variety of chemicals (pesticides, insecticides etc.), or environmental factors (DO, pH, temperature, salinity, etc) affecting different biological processes in fish. The present review discusses some of such stressors and their effects on fish from a wide range of literature available across last four decades. The metabolic pathways involved in terms of energy homeostasis and ATP production during stress exposure in fish is a new addition here, and has been addressed to some extent in case of temperature and salinity stress.